2016
DOI: 10.1080/08941939.2016.1241324
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio on Appendectomy of Geriatric and Nongeriatric Patients

Abstract: NLR could not predict positive appendectomy rates in the geriatric population but could in the nongeriatric patient group. To find the optimal NLR levels, prospective randomized studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The NLR as an inflammatory marker has proven its association with complications and long-term outcome in the setting of gastro-intestinal pathologies treated medically or surgically [ 6 , 9 – 11 ]. The NLR has also been associated with complications after major cardiac events or in a variety of cancers [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NLR as an inflammatory marker has proven its association with complications and long-term outcome in the setting of gastro-intestinal pathologies treated medically or surgically [ 6 , 9 – 11 ]. The NLR has also been associated with complications after major cardiac events or in a variety of cancers [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…White blood cell count (WBC) is studied well in the literature, but recently, there are several CBC parameters such as red blood cell distribution width (RDW), mean platelet volume (MPV), and platelet distribution width (PDW) associated with the diagnosis of appendicitis (8)(9)(10)(11). In recent studies, neutrophil-to-lymphocyte ratio (NLR) is reported associated with several surgical clinical conditions as appendicitis, acute mesenteric ischemia, and strangulated inguinal hernia (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…They found that diagnostic values for diagnosing acute appendicitis were increased when the cut-off value decreased (32) . Cigsar et al found the cut-off value of NLR as 4.9 by the evaluation of ROC curve analysis in their series, the sensitivity and specificity were found to be 73% (33) . In our study, when the cut-off value was taken as 5.80 in the group of patients who were aged 60 years and older, the sensitivity was found to be 69.1%, specificity was 52.7%, the positive predictive value was 70.2% and the negative predictive value was calculated as 52.3%.…”
Section: Discussionmentioning
confidence: 92%